Understanding the policy landscape for climate action in Kenya: Potential for integration of gender, nutrition, and improved impact monitoring - Magalhaes, Marilia; Bryan, Elizabeth; Ringler, Claudia; Nyukuri, Elvin; Choudhury, Zahid ul Arifin (International Food Policy Research Institute, 2025)
As in other low- and middle-income countries, more intense climate hazards and a warmer climate negatively impact agricultural production and livelihoods of smallholder farmers in Kenya, as well as household diets, national food security and gender equality. Improving climate policy and investments to address these negative impacts requires suitable policy and investment structures that are, moreover, adequately networked among each other and with equity and nutrition efforts for effective climate action. This paper explores the institutional arrangements of the climate change policy landscape in Kenya by mapping governmental and non-governmental actors involved in climate action and how connected and influential they are. Data for this paper was collected through two participatory workshops, one at the national level and one at the county level, using the Net-Map approach. This approach provides novel insights into the highly complex climate policy landscape in Kenya. Although several climate policies and actions are in place in the country, workshop participants called for better coordination across climate change actors and stronger implementation capacity. The recent structural changes in the donor landscape might be an entry point for better alignment and coordination among different actor groups, and specifically among different government actor groups. A lack of operational monitoring and evaluation systems was also considered an important impediment to assess to what extent women and other vulnerable groups are benefitting from climate action in the country.